Comparitive Study of Two ZLD Treatment Plants - Sahithya , D. Devi; Lakshmi , M. V. V. Chandana (International Journal of Membrane Science and Technology, 2023)
Due to the increased demand for water over the past ten years, the recovery and recycling of wastewater has become a major trend. An ambitious wastewater management technique known as ZLD aims to completely remove all liquid wastes from leaving the plant or facility boundaries, with the bulk of water being recovered for reuse. This system uses cutting-edge scientific water treatment procedures to reduce the amount of liquid waste produced at the conclusion of your industrial process to zero, which is both effective and environmentally friendly. It is a procedure that benefits industrial, municipal and environmental groups because no effluent or discharge is generated. The treatment of industrial wastewater from two different companies was examined in this study over an 8-month period utilizing two ZLD treatment plants. Two ZLD processes were identical, but they were differed at two steps where batch evaporator and rotary kiln replaced each other with MEE and ATFD. In order to assess which process is reliable, two ZLD treatment plants were evaluated in terms of quantity, time, steam consumption, power consumption, and operational cost.